Золотоординські "темні" віки на землях південної Русі: історичноархеологічний контекст - Моця, О.П. (Археологія, 2017)
Золотоординський період вітчизняної історії (1241— 1362 рр.) відзначений суттєвими змінами в житті слов’ян-автохтонів, пов’язаний, насамперед, із навалою орд хана Батия та загибеллю Києворуської держави. Події, що відбулися, безперечно, залишили слід у пам’ятках матеріальної культури. Проведений на їх основі аналіз дозволяє стверджувати, що т. зв. «темні» віки, насправді не були аж такими «темними». The historic period between the 1240s and the 1360s in homeland history is a time of the Eastern Slavs’ subjection to the Mongol and Tatar conquerors at the south of former Kyiv Rus. It is often called the «Dark Ages»; and there is comparatively few information about it in the written sources of that time. However, in view of intensive accumulation of archaeological information in recent decades, the situation has significantly changed. First of all, it concerns migration of new ethnic groups into the lands of the Black Sea north region from the eastern regions: the Volga River region, the Northern Caucasus, an other regions which already have got into dependence on the Mongols and Tatars. There were also micro migrations among the autochthons, namely, the Eastern Slavs who earlier lived on the Ancient Rus state territory. Significant for these centuries was the formation of the relations on the trade routes with traffic guaranteed by the Ghengizids, the Great Ghengiz Khan’s relatives. The descendants of his eldest son were his representatives in Ulus of Jochi. One of the results of this fact was appearance of so-called steppe cities, urban centres absolutely untypical for other nomad societies. Besides, such contacts are evidenced also by numerous elements of also untypical for these places features of material culture (ceramics and other crafts, coins, and other artefacts). The Slavs contacted with the newcomers, but probably in most cases these interrelations were peaceful. It is evidenced by the lack of fortifications at the Slavs’ sites, as well as by mixed anthropological structure of the population in various regions of the modern Ukrainian territory. It also should be noted that Ancient Rus lands did not indirectly formed Ulus of Jochi, but were under the conquerors’ control. As a whole, the «Dark Ages» being studied in more detail at an up to date scientific level appear to be not so «dark», though acquiring the further study. Исторический период отечественной истории между 40-ми годами ХІІІ в. и 60-ми годами ХІV в. — время подчинения восточных славян монголо-татарским завоевателям на юге бывшей Киевской Руси. Часто его именуют «темными» веками, о которых сохранилось относительно немного информации в письменных источниках того времени. Но в связи с интенсивным накоплением археологической информации в последние десятилетия ситуация существенно изменилась. В первую очередь, это касается переселения на земли Северного Причерноморья новых этнических групп из восточных районов — Поволжья, Северного Кавказа и иных регионов, уже ранее попавших под зависимость от монголо-татар. Также происходили микромиграции среди автохтонов — восточных славян, ранее проживавших на древнерусской государственной территории. Существенным для этих столетий стало формирование связей на торговых путях, передвижение по которым было гарантировано со стороны Чингизидов — родственников великого Чингисхана, представителем которого в Улусе Джучи являлись наследники его старшего сына. Одним из результатов этого стало появление так называемых степных городов — урбанистических центров, совершенно нетипичных иным кочевническим обществам. Кроме того, о таких контактах говорят и многочисленные элементы также нетипичных для этих мест элементов материальной культуры (керамика и иные ремесленные изделия, монеты и другие артефакты). Славяне вступали в различные контакты с пришельцами, но, вероятно, в большинстве случаев это были мирные взаимоотношения. Об этом говорит отсутствие укреплений на славянских памятниках, а также смешанный антропологический состав населения в разных районах территории современной Украины. Нужно отметить и то, что древнерусские земли непосредственно в Улус Джучи не входили, но пребывали под контролем завоевателей. В целом же, «темные» века при их более детальном изучении на сегодняшнем научном уровне, оказываются не такими уж «темными», хотя и заслуживают дальнейшего изучения.